SC17 Debriefing a major incident exercise. (3rd November 2019) - Blackmore, Andrew; Griscti, Reuben; Wright, Dave; Purva, Makani
Abstract : Background: The Civil Contingencies Act (2004) requires organisations such as the emergency services, councils and hospital trusts to prepare for emergencies by undertaking 'live' Major Incident exercises every three years¹. In the summer of 2017 our organisation took part in 'Operation Orange Falcon, ' a multiagency live Major Incident Exercise. This involved teams from Hull and East Yorkshire Hospitals, Yorkshire Ambulance Service, Humberside Fire and Rescue, Humberside Police and the Royal Logistics Corps and more than 60 casualty volunteers. Hull Institute of Learning and Simulation (HILS) led the debriefing element of the exercise. Project summary: The challenge in debriefing such a large-scale exercise came in providing meaningful immediate feedback to participants while also providing useful feedback to the involved organisations as a whole. We approached this by using two forms of debriefing; a 'hot debrief' on closing the exercise and a 'cold debrief' several weeks later. It was impractical to deliver a hot debrief to all of the participants in the exercise together. We agreed within the participating organisations to establish key areas of focus and placed debriefing teams in each of those key areas. They could then provide immediate feedback to participants on close of exercise. The debriefing teams consisted of a content expert, with expertise in the particular area being observed and an experienced debriefer from HILS. The agreed areas of focus included: Decontamination at the scene of the incident. The incident command team on–site. Decontamination at the hospital. Triage at the Hospital. Hospital control room. Casualty volunteers were debriefed separately by a team that included a psychologist from the Humber Mental Health Trust. The cold debrief was held eight weeks after the exercise and all participants were invited to attend. It focused on the same key areas, with the addition of video footage of the day to illustrate key points and revisited the issues raised in the hot debriefings. Results: The feedback from the other agencies was very positive. They reported that the standard debriefings they had attended before focused on finding fault or assigning blame. Use of on-site hot debriefing provided a deeper understanding of how the Trust's Major Incident Plan worked in practice. Discussion: The skills of debriefers from a healthcare background can be transferred outside of the healthcare environment when paired up with content experts in the field. Debriefing teams improved the experience of participants in a multiagency Major Incident Exercise. References: Cabinet Office. 'Emergency Preparedness: Guidance on Part 1 of the Civil Contingencies Act 2004, its Associated Regulations and Non - statutory Arrangements . ' (2005).